RESPON PERTUMBUHAN DAN PRODUKSI EMPAT VARIETAS KEDELAI (Glycine max L.) TERHADAP TINGKAT NAUNGAN - Muhammad Afandi Muhammad Afandi; Lisa Mawarni; Syukri Syukri (Jurnal Agroekoteknologi, 2013)
The Response of Growth and Yield of  Four Soybean Varieties (Glycine max L.) to The Shading Levels,The aim of the study was to obtain the effect of soybean seed size on the  shading levels for growth and yield of soybean (Glycine max L.) The study was conducted at Tanjung Selamat village at 57 metres above sea level, from April to July 2012. The  split plot design was used two treatment, namely shading level  a N0 (no shading), N1 (shading 20%), N2 (40% shading), and N3 (60% shading) as main plot and four varieties V1 (Anjasmoro), V2 (Burangrang), V3 (Wilis), and V4 (Rinjani) as sub plot. The results showed that shading level significantly affected germination percentage, plant height 2-5 Weeks After Planted, number of branches, number of chlorophyll, total leaf area, number of  fill pods, and production per  twelve plants. The soybean varieties significantly affected plant height ages 2-5 Weeks After Planted, number of chlorophyll, number of branches, flower initiation, number of fill pods, production per twelve plants, and weight of 100 seeds. Interaction of two treatments significantly affected production per twelve plants.   Keywords: soybean, shade, and varieties